Visual perception of multi-column-layout text: insight from repeated and non-repeated reading. Issue 1 (2nd January 2017) - Al-Samarraie, Hosam; Sarsam, Samer Muthana; Umar, Irfan Naufal
ABSTRACT: Information processing speed affects reading performance and interaction with text. Understanding how column type in an online context influences reading effectiveness can help us to identify less effective layouts. This study explored the visual perception of 23 participants while they read text arranged in a multi-column layout. Two tasks (repeated reading and non-repeated reading) were designed and assessed to have the same level of difficulty. Information was organised according to three types of column layout (one, two, or three columns). Eye movement analysis showed that participants performed best in a three-column layout for repeated reading, and with one column for normal reading. We also found that the repeated reading technique reduced readers' distraction and therefore increased their visual performance, which in turn increased information processing, regardless of column layout. These findings with regard to single- and multi-column layouts can help suggest effective reading configurations for online readers and provide insights for human–computer interaction theories on human interaction with different typographic elements.